Relationship Between Handgrip Strength with the 6-Minute Walking Test Distance in Heart Failure Patients - Hamdani, Rita; Florencia Leona, Denada (Yayasan Literasi Sains Indonesia, 2023)
Heart failure is a complex clinical syndrome characterized by objective evidence of an underlying structural abnormality or cardiac dysfunction that reduces the ability of the ventricles to fill or pump blood. One of the essential indicators in evaluating the condition of heart failure patients in treatment undergoing a cardiovascular rehabilitation program is an assessment of the ability to perform physical activity. Evaluation of physical activity ability can be determined through exercise capacity assessments such as the 6-minute walk test and Handgrip strength method. The aim of this study was to determine the relationship between handgrip strength and the distance travelled in a 6-minute walking test in patients with heart failure. This was a cross-sectional study of 55 heart failure patients at the Integrated Heart Center Department of RSUP Dr M. Djamil Padang from February 2022 to December 2022. Based on the Pearson correlation test, there was a statistically significant result between handgrip strength and distance in the 6-minute walking test with a P value of 0.01 (p<0.05). There is a positive and statistically significant relationship between handgrips strength with a 6-minute walking test distance in heart failure patients.